2015
DOI: 10.1017/s0022377815000197
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the generation and properties of laboratory-produced ball lightning

Abstract: The experiments revealed that ball lightning is a self-confining quasi-neutral in a whole plasma system that rotates around its axis. Ball lightning has a structure of a spherical electric domain, consisting of a kernel with excess negative charge and an external spherical layer with excess positive charge. The excess of charges of one sort and the lack of charges of the other sort in the kernel or in the external spherical layer significantly reduces the possibility of electron capture by means of an electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…The phenomenon of anomalous passing the radiation through solid body targets is also observed in laser physic-a fluxes of fast particles (including relativistic protons, electrons, and positrons) and a magnetic field from the back side of the target were registered in a number of experiments at intense interaction of laser radiation with the target [20] [21]. The phenomenon of the anomalous ball lightning penetration or super-passability was detected in the experiments [14] [22] is in some sense similar to the known phenomenon of helium super-fluidity, as noted in [10]. But in this case entirely different physical processes occur.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…The phenomenon of anomalous passing the radiation through solid body targets is also observed in laser physic-a fluxes of fast particles (including relativistic protons, electrons, and positrons) and a magnetic field from the back side of the target were registered in a number of experiments at intense interaction of laser radiation with the target [20] [21]. The phenomenon of the anomalous ball lightning penetration or super-passability was detected in the experiments [14] [22] is in some sense similar to the known phenomenon of helium super-fluidity, as noted in [10]. But in this case entirely different physical processes occur.…”
Section: Introductionmentioning
confidence: 92%
“…This model also contradicts the high-energy ball lightning model [4] [6] [17] [18]. It should be noted that in a number of experiments carried out in [10] [14] [18] with a laboratory produced ball lightning the holes in glass were not observed.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Any model of BL (electrostatic, electrochemical, charged aerosols and fractals, nuclear, plasma, etc. ; for reviews see Donoso et al, 2006;Oreshko, 2015) must predict all the reported characteristics of BL. Moreover, any experiment to generate BL must fully replicate its properties (for reviews see Bychkova et al, 2016;Stephan et al, 2016;Wu, 2016).…”
Section: Introductionmentioning
confidence: 99%